Neuropathologic Characterization of Pontocerebellar Hypoplasia Type 6 Associated With Cardiomyopathy and Hydrops Fetalis and Severe Multisystem Respiratory Chain Deficiency due to Novel RARS2 Mutations. Issue 7 (July 2015) - Lax, Nichola Z.; Alston, Charlotte L.; Schon, Katherine; Park, Soo-Mi; Krishnakumar, Deepa; He, Langping; Falkous, Gavin; Ogilvy-Stuart, Amanda; Lees, Christoph; King, Rosalind H.; Hargreaves, Iain P.; Brown, Garry K.; et al.
<x xml:space="preserve">Abstract</x> Abstract Autosomal recessive mutations in the RARS2 gene encoding the mitochondrial arginyl-transfer RNA synthetase cause infantile-onset myoencephalopathy pontocerebellar hypoplasia type 6 (PCH6). We describe 2 sisters with novel compound heterozygous RARS2 mutations who presented perinatally with neurologic features typical of PCH6 but with additional features including cardiomyopathy, hydrops, and pulmonary hypoplasia and who died at 1 day and 14 days of age. Magnetic resonance imaging findings included marked cerebellar hypoplasia, gyral immaturity, punctate lesions in cerebral white matter, and unfused deep cerebral grey matter. Enzyme histochemistry of postmortem tissues revealed a near-global cytochrome c oxidase-deficiency; assessment of respiratory chain enzyme activities confirmed severe deficiencies involving complexes I, III, and IV. Molecular genetic studies revealed 2 RARS2 gene mutations: a c.1A>G, p.? variant predicted to abolish the initiator methionine, and a deep intronic c.613-3927C>T variant causing skipping of exons 6–8 in the mature RARS2 transcript. Neuropathologic investigation included low brain weights, small brainstem and cerebellum, deep cerebral white matter pathology, pontine nucleus neuron loss (in 1 sibling), and peripheral nerve pathology. Mitochondrial respiratory chain immunohistochemistry in brain tissues confirmed an absence of complexes I and IV immunoreactivity with sparing of mitochondrial numbers. These cases expand the clinical spectrum of RARS2 mutations, including antenatal features and widespread mitochondrial respiratory chain deficiencies in postmortem brain tissues.